2013
DOI: 10.1093/humrep/det087
|View full text |Cite
|
Sign up to set email alerts
|

Do endometriomas induce an inflammatory reaction in nearby follicles?

Abstract: This paper reveals that endometriomas seldom induce inflammation in nearby follicles during IVF; therefore, routine cystectomy prior to IVF may not be necessary. Cytokine levels in the follicular fluid, nonetheless, show distinctive patterns and increased levels may be linked to reduced ovarian response independent of the cause of infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 38 publications
2
33
0
2
Order By: Relevance
“…These data suggest that an EM might not affect the environment of follicle growth. This result agrees with a recent report, which showed no differences in cytokine concentrations in the FF from ovaries with or without an EM [24].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These data suggest that an EM might not affect the environment of follicle growth. This result agrees with a recent report, which showed no differences in cytokine concentrations in the FF from ovaries with or without an EM [24].…”
Section: Discussionsupporting
confidence: 94%
“…With most endometriomas, there is no evidence of increased cytokine concentration in the ipsilateral leading follicle. Infrequently, the concentration of inflammatory cytokines is increased in the FF [24].…”
Section: Discussionmentioning
confidence: 99%
“…TNFa is a pro-inflammatory cytokine released by macrophages and its production can be induced by VEGF. It has a role in proliferation of granulosa cells and enhances its IL8 secretion (Kilic et al 2007, Opøien et al 2013. TNFa level is significantly higher in FF associated with poor quality oocytes and embryos (Wunder et al 2006).…”
Section: Cytokines In Human Ffmentioning
confidence: 99%
“…Therefore, it is thought that granulosa cell and theca cell IL8 secretion is associated with follicle growth, oocyte maturation and ovulation, rather than being solely the result of hormonal stimulation (Runesson et al 2000). IL8 seems to vary inversely with IL10, IL12 and TNFa, indicating that immune cells may interact with granulosa cell function (Opøien et al 2013). IL8 levels in FF are not associated with fertilization and implantation rates or IVF outcome (Gazvani et al 2000).…”
Section: Cytokines In Human Ffmentioning
confidence: 99%
“…However, whether ovarian surgical interventions will reduce ovarian reserves and responsiveness to stimulation is still a controversial issue. Some studies have shown that endometriomas will not damage ovarian reserves[1] and rarely damages oocyte quality[2]. Moreover, the excision of endometriomas can improve the success rate of ART[3].…”
Section: Introductionmentioning
confidence: 99%